EKSPANSI “TRUST” DALAM EVALUASI PENDIDIKAN MENITI KREADIBILITAS HASIL BELAJAR - Ali Akbarjono (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2017)
Evaluation of Education is as a subsystem of implementing management of education that  positionedas an educational institution having  a centralistic position and becoming a media that accommodates the public assessment of the  outcomes (output and  outcome) achieved. Through the  optimization of education evaluation evaluation has a positive impact on the cultivation of the values  of public trust  as one  of the factors  that  contribute to the success of management of an educational institution because without buliding and  actualizing trust  well,   the  public only as a spectator who has apathy character of the effort of quality development both ranging from input quality, process and output. Ideally  the  implications of optimizing the  implementation of the  evaluation mechanism of education can  be an instrument of the process of comparing the existing  situation with certain criteria to the problems associated with academic in an educational institution because the evaluation of education is actually not only assessing the learning outcomes of students in a certain level of education, regarding the assessment of various aspects affecting the student’s learning process, such as evaluation of teachers, curriculum, methods, means of infrastructure, environment and so on. In general the scope of evaluation in the field of education in schools includes three main components namely: Evalua- tion of teaching programs, Evaluation of teaching implementation process, and Evaluation of learning outcomes. .